Phospholipase C and diacylglycerol mediate olfactory responses to amino acids in the main olfactory epithelium of an amphibian. - Alfredo Sansone (Public Library of Science (PLoS), 2014)
The semi-aquatic lifestyle of amphibians represents a unique opportunity to study the molecular driving forces involved in the transition of aquatic to terrestrial olfaction in vertebrates. Most amphibians have anatomically segregated main and vomeronasal olfactory systems, but at the cellular and molecular level the segregation differs from that found in mammals. We have recently shown that amino acid responses in the main olfactory epithelium (MOE) of larval Xenopus laevis segregate into a lateral and a medial processing stream, and that the former is part of a vomeronasal type 2 receptor expression zone in the MOE. We hypothesized that the lateral amino acid responses might be mediated via a vomeronasal-like transduction machinery. Here we report that amino acid-responsive receptor neurons in the lateral MOE employ a phospholipase C (PLC) and diacylglycerol-mediated transduction cascade that is independent of Ca(2+) store depletion. Furthermore, we found that putative transient receptor potential (TRP) channel blockers inhibit most amino acid-evoked responses in the lateral MOE, suggesting that ion channels belonging to the TRP family may be involved in the signaling pathway. Our data show, for the first time, a widespread PLC- and diacylglycerol-dependent transduction cascade in the MOE of a vertebrate already possessing a vomeronasal organ.